Study of Necessities and Technologies for Using Hybrid Photovoltaic-Wind Power Systems - Sobhan Dorahaki (Institute of Advanced Engineering and Science, 2015)
In recent years, increase in environment concerns and demand for energy are two main issues in ongoing growth of using solar systems. Solar energy has been known as a renewable and clean energy source. One of the most applied and new ways for using sun energy is hybrid photovoltaic technology. This paper discusses requirements, methods, limitations and technologies used in the hybrid photovoltaic-wind power system.